2020
DOI: 10.1101/2020.06.29.175877
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Global profiling of the crotonylome in Small Cell Lung Cancer

Abstract: AbstractSmall cell lung cancer is a deadly neuroendocrine lung cancer subtype, which harbors the driver mutations of RB1 and TP53 as well as EP300/CREBBP. Since CREBBP/p300 are two prominent crotonyl-CoA transferases responsible for the global crotonylation in cells, here we investigated the crotonylome in SCLC tissues compared with normal lung tissues through TMT labeling coupled with LC-MS/MS and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 18 publications
(16 reference statements)
0
1
0
Order By: Relevance
“…When comparing small cell lung tissues with paired normal lung tissues from different patients, several tumor metastasis and tumor microenvironment regulators, such as caveolin-1, platelets, endothelial cell adhesion molecule 1, and stathmin 1 (STMN1), are modified by Kcr, underlying the broad spectrum of functions of Kcr-modified proteins in small cell lung cancer (SCLC). Additionally, the authors showed that crotonyl-CoA transferases, including KAT2A, KAT8, and p300, exhibit relatively higher expressions in SCLC, while only p300 had a positive overall survival in the Kaplan–Meier survival analysis [ 161 ]. Additionally, it is well known that M2-polarized tumor-associated macrophages are responsible for cancer progression and metastasis and promote the migration and invasion of lung cancer cells, resulting in decreased overall survival in tumor-bearing mice [ 162 ].…”
Section: Roles Of Novel Acylations In Tumor Metastasesmentioning
confidence: 99%
“…When comparing small cell lung tissues with paired normal lung tissues from different patients, several tumor metastasis and tumor microenvironment regulators, such as caveolin-1, platelets, endothelial cell adhesion molecule 1, and stathmin 1 (STMN1), are modified by Kcr, underlying the broad spectrum of functions of Kcr-modified proteins in small cell lung cancer (SCLC). Additionally, the authors showed that crotonyl-CoA transferases, including KAT2A, KAT8, and p300, exhibit relatively higher expressions in SCLC, while only p300 had a positive overall survival in the Kaplan–Meier survival analysis [ 161 ]. Additionally, it is well known that M2-polarized tumor-associated macrophages are responsible for cancer progression and metastasis and promote the migration and invasion of lung cancer cells, resulting in decreased overall survival in tumor-bearing mice [ 162 ].…”
Section: Roles Of Novel Acylations In Tumor Metastasesmentioning
confidence: 99%